Welfare, labor supply and heterogeneous preferences: Evidence for Europe and the US - Olivier Bargain; André Decoster; Mathias Dolls; Dirk Neumann; Andreas Peichl; Sebastian Siegloch (Institute for the Study of Labor (IZA), 2011)
Following the report of the Stiglitz Commission, measuring and comparing well-being across countries has gained renewed interest. Yet, analyses that go beyond income and incorporate non-market dimensions of welfare most often rely on the assumption of identical preferences to avoid the difficulties related to interpersonal comparisons. In this paper, we suggest an international comparison based on individual welfare rankings that fully retain preference heterogeneity. Focusing on the consumption-leisure trade-off, we estimate discrete choice labor supply models using harmonized microdata for 11 European countries and the US. We retrieve preference heterogeneity within and across countries and analyze several welfare criteria which take into account that differences in income are partly due to differences in tastes. The resulting welfare rankings clearly depend on the normative treatment of preference heterogeneity with alternative metrics. We show that these differences can indeed be explained by estimated preference heterogeneity across countries' rather than demographic composition.
urn:nbn:de:101:1-201111213404
Keywords: C35; D63; H24; H31; J22; 330; welfare measures; preference heterogeneity; labor supply; Beyond GDP; Wohlfahrtsanalyse; Sozialer Indikator; Präferenztheorie; Arbeitsangebot; Freizeit; Kulturelle Identität; Schätzung; Europa; USA